Faecal immunochemical test mitigates risk of delayed colonoscopy in people with elevated risk of colorectal neoplasia. Issue 6 (16th March 2022) - Wassie, Molla M; Young, Graeme P; Cock, Charles; Bampton, Peter; Winter, Jean M; Simpson, Kalindra; Saluja, Hariti; Chuang, Anthony; Fraser, Robert J; Symonds, Erin L
Abstract: Background and Aim: Surveillance colonoscopies may be delayed because of pressure on resources, such as the COVID‐19 pandemic. This study aimed to determine whether delayed surveillance colonoscopy increases the risk for advanced neoplasia and whether interval screening with faecal immunochemical tests (FITs) and other known risk factors can mitigate this risk. Methods: A retrospective cohort study of individuals undergoing surveillance colonoscopy for personal or family history of colorectal neoplasia was being provided with FIT between colonoscopies. Colonoscopy ≥ 6 months after the guideline‐recommended interval was considered "delayed." Individuals were stratified based on prime colonoscopy findings to nonneoplastic findings, non‐advanced adenoma, and advanced adenoma. The relative risk (RR) for developing advanced neoplasia was determined using a robust multivariable modified Poisson regression. Results: Of 2548 surveillance colonoscopies, 1457 (57.18%) were delayed. Prior advanced adenoma, older age (> 60 years) and nonparticipation in interval FIT were associated with increased risk for advanced neoplasia ( P < 0.05). There was a trend to increased risk in those with prior advanced adenoma with an increasing colonoscopy delay ( P trend = 0.01). In participants who did not complete interval FIT and having advanced adenoma in the prime colonoscopy, risk of advanced neoplasia was 2.48 times higher (RR = 2.48, 95% confidence interval: 1.20–5.13) in participants who had beyond 2 years of delayed colonoscopy compared with those with on‐time colonoscopy. Colonoscopy delay did not increase the risk of advanced neoplasia in participants with negative interval FIT results. Conclusion: Surveillance colonoscopy can be safely extended beyond 6 months in elevated colorectal cancer risk patients who do not have prior advanced adenoma diagnosis, particularly if interval FIT is negative.